Увічнення пам'яті М. С. Грушевського в Україні в пам'ятках монументального мистецтва - Скрипник, П. (Краєзнавство, 2016)
На основі вивчення творчої спадщини, а також досліджень з увічнення пам'яті, в статті висвітлено питання вшанування пам'яті видатного вченого та громадського діяча М.С. Грушевського. Його діяльність протягом життя, а також по смерті привертали увагу української громадськості, були зразком для наслідування. Однією з форм увічнення пам'яті М.С. Грушевського в пам'ятках монументального мистецтва є спорудження пам'ятників на його честь. Історія їх спорудження має велике значення у плані формування національної свідомості в Україні, а також тривалу і повчальну історію. На основе изучения творческого наследия, а также исследований по увековечиванию памяти, в статье освещены вопросы увековечивания выдающегося учёного и общественного деятеля М.С. Грушевского. Его деятельность в течение жизни, а также по смерти привлекали пристальное внимание общественности, были образцом для подражания. Одной из форм увековечивания памяти М.С. Грушевского в памятниках монументального искусства является сооружение памятников на его честь. История их создания имеет большое значение в плане формирования национального самоcознания в Украине, а также длительную и поучительную историю. Statement of the problem. In 2016 Ukraine and the Ukrainian diaspora abroad will commemorate a jubilee – the 150th anniversary of the birth of Mykhailo Hrushevsky, a prominent scholar and public figure. In this context, a tribute to his memory is becoming an important focus. One of the forms of such commemoration is the erection of monuments to M.S. Hrushevsky in Ukraine. So, systematization and generalization of the data on their erection are at issue. The high relevance of the subject is due to the fact that the erection of monuments to M. Hrushevsky is closely tied to the formation of Ukrainian statehood both during the Soviet rule and in the years of Ukraine’s independence. A relatively peaceful attainment of Ukrainian independence in 1991caused a major opposition of anti-Ukrainian forces to the formation of the Ukrainian state, as well as the national awareness of its people. Since M. Hrushevsky was a symbol of the Ukrainian statehood, the struggle for his legacy has never ceased. It is for this reason that the coverage of the tributes to his memory is of high relevance, especially during the war unleashed by the Russian Federation against Ukraine. The relation of the subject to academic or practical tasks. The article has been written in the framework of Ukrainian community’s preparation to marking the 150th anniversary of M. Hrushevsky. It implies continued coverage of the subject in mass media. The analysis of recent studies and publications. M.Hrushevsky’s personality has always attracted attention of every common Ukrainian. Yet, the war declared to M.Hrushevsky and his family after his death by the Soviet authorities affected the studies of his scholarly legacy. The works of the Great Ukrainian were moved from library shelves to secret repositories. Every measure was taken to discredit or destroy physically the representatives of M. Hrushevsky’s historical school. They were labeled as “Ukrainian bourgeois nationalists”, spies, enemies of Ukrainian people. M. Hrushevsky was only permitted to be mentioned in a highly critical manner. At that one did not need to study his scholarly heritage but had to echo the well-rooted “terminology” of the ideology department of the CPSU Central Committee. That situation persisted till the declaration of Ukraine independence in 1991. During that period, studies and commemoration of M. Hrushevsky’s activities moved outside Ukraine. In 1965 the Ukrainian Historical Association (UHA) was established in the USA; it played a major role in researching and popularizing M. Hrushevsky’s ideological legacy. Through the efforts of Professor Lubomyr Wynar, the UHA set up a specialized scholarly area – Hrushevsky studies. The UHA held both academic conferences commemorating M. Hrushevsky’s jubilees and special Hrushevsky readings. Under the UHA a journal was founded – Ukrainian Historian, which for nearly 50 years has covered different aspects of Ukrainian history, M. Hrushevsky’s scholarly heritage included. It also presented information about the erection of the tombstone on Hrushevsky’s grave in Kyiv. Besides, L. Wynar authored and edited quite a number of publications covering various periods of M. Hrushevsky’s life. Since 1990-ies, the studies of Hrushevsky’s legacy began in Ukraine. Published were collections of documents and certain materials that depicted life and scholarly activities of M. Hrushevsky. Information started to appear (mainly in periodicals) about monuments to M. Hrushevsky being erected. The systematic picture concerning this issue, however, is still lacking. So, relying on the materials presented, the author has made an attempt to fill that gap. The objective of the present study is to systematize and generalize the data on the erection of monuments to M. Hrushevsky in Ukraine.